Effects of Combined Interventions with Aerobic Physical Exercise and Cognitive Training on Cognitive Function in Stroke Patients: A Systematic Review - Amorós-Aguilar, Laura (Brain Sci, 2021)
(1) Background: Stroke is a major cause of permanent disability in multiple functions, including the cognitive domain. Since both cognitive training and aerobic physical exercise may exert positive effects on cognition after stroke, one may expect synergistic benefits when combining both interventions. (2) Methods: We carried out a systematic search of studies testing, in adult stroke patients, whether structured aerobic exercise combined with cognitive training led to higher cognitive benefits than either of these interventions when applied singly, or than interventions not including aerobic exercise or cognitive training. (3) Results: Five fair-quality randomized controlled trials fulfilled the search criteria. Exercise intensity was moderate-vigorous and cognitive training was mainly computer-based. The studies were heterogeneous regarding the cognitive tests used, and for this reason, a meta-analysis was not performed. Only three studies included follow-up assessment. The combined intervention was associated with pre-post improvement in at least one cognitive test in all the studies, and with higher positive effects compared to other conditions (although statistical significance was not always reached) in four studies. (4) Conclusions: Further trials including a long-term follow-up and comprehensive neuropsychological testing should be undertaken to determine whether combined aerobic exercise and cognitive training leads to additive cognitive benefits after stroke.